Glyphosate resistance in Kochia (Kochia scoparia) - Waite, Jason Charles (Kansas State University, 2010)
Kochia (Kochia scoparia (L.) Schrad) is a troublesome weed throughout the western United States and Great Plains. It is an aggressive warm season annual dicot plant that exhibits protogynous flowering and facultative open pollination. The aggressive growth habit and prolific seed production enable kochia to spread and compete well for light, moisture, and nutrients. Kochia is ranked as one of the most problematic weeds in cultivated fields including corn, sorghum, wheat, soybean, and sugarbeet. Kochia has been found to lower yields as well as hinder mechanical harvest. Glyphosate is a nonselective herbicide that is widely used in controlling kochia in no-till cropping systems. With rapid adoption of no-till systems where glyphosate is used for weed burndown treatment before planting and extensive use of glyphosate resistant crops, it is common that glyphosate is frequently applied on the same field during the growing season. In 2007, poor control of kochia was observed in three fields in Western Kansas. Greenhouse experiments were conducted with 10 kochia populations to determine the efficacy of glyphosate on kochia when applied at 10 different rates and at 3 plant heights. Herbicide rates included 0, 0.0625, 0.125, 0.25, 0.50, 1, 1.5, 2, 4 and 6 times a typical use rate of 870 g ae/ha. Resistance to glyphosate was identified in three kochia populations. The glyphosate resistant populations from Ingalls, Norton, and Moscow Kansas were 4.6, 3.3, and 2.8 times more resistant to glyphosate than a susceptible population, respectively, based on the rate required for 50% control. Glyphosate injury symptoms included stunting, and chlorosis, followed by some necrotic tissue but resistant plants generally recovered from injury, or were slow to show symptoms. In general, the level of resistance is greater in more developed plants compared to younger plants. Experiments also were conducted on the different kochia biotypes to evaluate glyphosate absorption and translocation, and any differences in mineral content of the plants that might be detrimental to glyphosate activity. Differences in glyphosate absorption and translocation and kochia mineral content were not sufficient to explain the resistance to glyphosate.
Keywords: Kochia scoparia; glyphosate; Agriculture, Agronomy (0285)